A formação continuada e os desenvolvimentos comportamental, socioemocional, motivacional e profissional dos docentes - Andrade, Laura Ferreira de (Universidade do Vale do Rio dos Sinos, 2021)
The dissertation bases the practice of a model of continuing education, implemented through the coaching methodology in the behavioral, socioemotional and motivational developments of the teachers. The empirical field is a private school of basic education in the metropolitan region of Porto Alegre. The basic authors of the study were Francisco Imbernón, Livia de Melo Barros, Helen Danyane S. CaetanoSouza, Vikki G. Brock e Edward L. Deci and Richard Ryan. Thus, the narrative that I bring is a society that undergoes changes in an accelerated way and the technologies have been presenting themselves more and more challenging, as well as also in constant transformation. Daily, we have followed these changes that have been reflected in people's lives and behavior, which invariably reflect in schools and inside classrooms. In this context, teachers become protagonists of a conceptual change without having the necessary preparation to deal with such transformations in students and in their own personal and professional lives. In this perspective, the main challenge of this study was to analyze the implementation of part of a model of continuing education in the researched school, through the coaching methodology and to demonstrate its contribution in the behavioral, socioemotional and motivational developments of the teachers. The adopted methodology was of qualitative approach and the data collection, subsidized of documental analysis of secondary source. During this study, I showed that the development of teachers in behavioral, socio-emotional and motivational issues occurred and that the coaching methodology, in the formative process, contributed significantly to this experience having more meaning, while generating reflection, self-knowledge, self-responsibility, among other themes that underpinned this continuing education. I conclude the research by proposing a propositional intervention for the improvement of continuing education, taking into account the basic themes that guided the study, also proposing the implementation of this training in other social contexts.
Keywords: Formação continuada; Coaching; Desenvolvimento; Motivação docente; Continuing education; Development; Teacher motivation; ACCNPQ::Ciências Humanas::Educação